Banks and the real economy: An assessment of the research - Berger, Allen N.; Molyneux, Phil; Wilson, John O.S. (Journal of Corporate Finance, 2020)
We review research on the effects of banks on the real economy, including, but not limited to articles in this Special Issue of the Journal of Corporate Finance. We focus primarily on US and European policy interventions that provide quasi-natural experiments with relatively exogenous shocks to bank output. We concentrate on single-country settings, avoiding potentially confounding differences in language, culture, law, currency, and so on, that complicate cross-country investigations. We also largely avoid the effects of financial crises, which are not exogenous to the banking system. The evidence strongly suggests positive effects of banks on the real economy.